Kinematic signatures of cluster formation from cool collapse in the Lagoon Nebula cluster NGC 6530. Issue 2 (22nd August 2019) - Wright, Nicholas J; Parker, Richard J
ABSTRACT: We examine the mass dependence of the velocity dispersion of stars in the young cluster NGC 6530 to better understand how it formed. Using a large sample of members we find that the proper motion velocity dispersion increases with stellar mass. While this trend is the opposite of that predicted if the cluster were developing energy equipartition, it is in agreement with recent N -body simulations that find such a trend develops because of the Spitzer instability. In these simulations the massive stars sink to the centre of the cluster and form a self-gravitating system with a higher velocity dispersion. If the cluster has formed by the cool collapse of an initially substructured distribution, then this occurs within 1–2 Myr, in agreement with our observations of NGC 6530. We therefore conclude that NGC 6530 formed from much more extended initial conditions and has since collapsed to form the cluster we see now. This cluster formation model is inconsistent with the idea that all stars form in dense, compact clusters and provides the first dynamical evidence that star clusters can form by hierarchical mergers between subclusters.